Imperfect birds : a novel - Lamott, Anne (Riverhead Books, 2010)
Rosie Ferguson is seventeen and ready to enjoy the summer before her senior year of high school. But as the school year draws to a close, there are disturbing signs that the life Rosie claims to be leading is a sham, and that Elizabeth's hopes for her daughter to remain immune from the pull of the darker impulses of drugs and alcohol are dashed. Now, Elizabeth is forced to confront the fact that Rosie has been lying to her, and that her deceptions will have profound consequences.